PENERAPAN DEEP LEARNING YOLO UNTUK PENGUKURAN JARAK OBJEK MENGGUNAKAN MONO KAMERA - Herdianto, Herdianto; Nasution, Darmeli; Atmaja, Niko Surya; Ramadhan, Syahrul (Universitas Methodist Indonesia, 2024)
Mobile robots are a type of robot that can move from one place to another. Therefore, this type of robot has been given the ability to detect objects and measure estimated distances to objects around it to then carry out actions to turn left and right, forward, backward or even stop to avoid collisions. In general, to measure the distance of objects on mobile robots, ultrasonic sensors such as the HC-SR04 are used and some also use cameras, although they can be used to measure distances, but the use of these sensors has disadvantages, such as the maximum distance that can be measured is 4 meters. Given this deficiency, the research that will be carried out will try a YOLO deep learning method that can detect objects and then measure the distance of objects around them. From the results of the tests that have been carried out, it is known that the distance to the object that can be measured is 31,400 mm with the actual object height being 1750 mm.